Stiffening near-net-shape functional parts of Inconel 718 LPBF considering material anisotropy and subsequent machining issues. (1st April 2022) - Pérez-Ruiz, José David; Marin, Felipe; Martínez, Silvia; Lamikiz, Aitzol; Urbikain, Gorka; López de Lacalle, Luis Norberto
Highlights: Iterative design methodology to improve the stiffness of LPBF components considering machining and anisotropy effects. Young's modulus improvement by evaluating the elastic anisotropy of different manufacturing configurations. Application to case study for finishing of thin-walled bent ducts. Abstract: Additive manufacturing of metallic parts has witnessed significant development. The laser powder bed fusion (LPBF) process has emerged as a key process for manufacturing thin-walled components. However, despite the significant advances, post-machining operations are required for the improvement of dimensional and surface quality, specifically in low stiffness components. This study proposed an iterative design methodology for improving the stiffness of such LPBF components. In the first stage, an initial assessment of the machining conditions was performed to obtain a first approach to the relationship between tooth passing, natural, and chatter frequencies. Thereafter, a method to improve Young's modulus was proposed by evaluating the elastic anisotropy of different manufacturing configurations. Furthermore, LPBF lateral stiffeners were included in the workpiece design, thereby converting the final workpiece into a temporary assembly. The proposed methodology was applied in a case study for finishing thin-walled bent ducts and a comparison for surface quality between stiffened and non-stiffened ducts using the proposed methodology was conducted. A significant roughness and cutting force reduction (≈50%) were obtained for the stiffened duct.